Assessment of CH4 and CO2 Emissions from a Municipal Waste Landfill: Trends, Dispersion, and Environmental Implications - Georgeta Olguta Gavrila; Gabriela Geanina Vasile; Simona Mariana Calinescu; Cristian Constantin; Gheorghita Tanase; Alexandru Cirstea; Valentin Stancu; Valeriu Danciulescu; Cristina Orbeci (Atmosphere)
The European Union views biogas production from landfills as a crucial element in achieving decarbonization goals by 2050. Biogas is primarily composed of methane (CH4) and carbon dioxide (CO2), produced through the anaerobic digestion of various residual materials. This study aimed to investigate CH4 and CO2 concentrations from municipal solid waste in biogas capture wells in a landfill in Romania between 2023 and 2024. A peak in CH4 concentrations occurred in the fall of 2024 (P4 well), while the highest CO2 content was recorded in the summer of 2023 (P3 well). The Aermod View software platform (version 11.2.0) was employed to model the dispersion of pollutants in the surrounding air. A worst-case scenario was applied to estimate the highest ground-level pollutant concentrations. The highest recorded CH4 concentration was 90.1 mg/m3, while CO2 reached 249 mg/m3 within the landfill. The highest CH4 concentrations were found in the southern part of the site, less than 1 km from the landfill, while CO2 was highest in the northern area. In conclusion, municipal solid waste landfills behave like unpredictable bioreactors, and without proper management and oversight, they can pose significant risks. An integrated system that combines prevention, reuse, and correct disposal is critical to minimizing these negative effects.